The Integration of Digital Interactive Whiteboards in Elementary School Education: A Literature Review Based on the TPACK Framework - Saputri, Kiki Niken; Anggraini, Ade Eka; Nusantara, Toto; Pristiani, Riska; Arifin, Slamet (Cybersecurity and Innovative Technology Journal, 2026)
This study seeks to analyze and synthesize the outcomes of previous studies about the implementation of PID in elementary education using the TPACK framework as a framework for analysis. This study is a review of scientific literature that analyzes ten scientific articles found in national and international scientific journals accessed via the Google Scholar, ERIC, and ScienceDirect databases. The technique utilized in analyzing the data involves collecting, coding, organizing, and synthesizing the information derived from the research. Based on the findings of this study, PK and TPK are identified as the most dominant dimensions of TPACK in the process of implementing PID in the classroom setting. On the other hand, TK and TCK were recognized as the weakest elements among the ten articles examined. It can be inferred from these findings that teachers are more at ease discussing instructional matters and integrating technology in their teaching methods, but still have issues in terms of technical proficiency in using devices and integrating technology in the curriculum content. In addition, it was also noted that teachers who used student-centered pedagogy effectively developed transformative TPACK, while teachers who utilized teacher-centered pedagogy failed to do so. Contextual knowledge (CK) has similarly been found to be an essential variable in moderating the effectiveness of PID implementation in various school contexts. In summary, the results obtained in this study prove that the effectiveness of PID implementation in elementary schools is not only contingent upon the presence of technology tools and their use in training sessions, but more importantly, the effective implementation of PID relies on the appropriate combination of all the seven TPACK components, especially TK and TCK, a student-centered instructional model, and careful considerations of the teaching and learning context. Finally, it is recommended that there should be more holistic, collaborative, and sustainable professional development programs for teachers, as well as future studies involving experimental and longitudinal research designs to investigate the effects of different TPACK training approaches in elementary schools.